The Girl from the Big Horn Country - Chase, Mary Ellen, 1887-1973; Elwell, Robert Farrington, 1874-1962 (Salt Lake City, UT : Project Gutenberg, 2013)
"The Girl from the Big Horn Country" by Mary Ellen Chase is a novel written in the early 20th century. The book centers around Virginia Hunter, a spirited young girl from the scenic Big Horn mountains in Wyoming, as she prepares to leave her home to attend school in the East, facing the challenges of new experiences far from her familiar surroundings. At the start of the novel, Virginia is deeply connected to her upbringing in the West, relishing the beauty of the Elk Creek Valley and the company of her cherished friends, particularly Donald Keith. As she bids farewell to her childhood home and contemplates her journey to Vermont, she grapples with a mix of excitement and homesickness. The initial chapter vividly describes her last day in Wyoming, highlighting her close relationships and the sense of belonging she feels to the rugged landscape, all while foreshadowing her upcoming adventures and the adjustments she must make in an unfamiliar environment. (This is an automatically generated summary.)
Release date is 2013-03-09
E-text prepared by Roger Frank
Keywords: Boarding schools -- Juvenile fiction; Girls -- Juvenile fiction; Vermont -- Juvenile fiction